The Impact of Project-Based Learning on 21st Century Skills in Teaching - Paudel, Shiva Prasad (Dhaulagiri Journal of Contemporary Issues, 2024)
This study is based on Project-Based Learning (PBL) in nurturing 21st-century skills among Class 9 mathematics students in Baglung, Nepal. Through teacher interviews and student focus groups, the study insight that PBL significantly enhances critical thinking by analyzing real-world data sets, improves problem-solving through practical applications in algebra and geometry, fosters collaboration in group projects related to mensuration and statistics, and strengthens communication skills through presenting mathematical solutions and findings. Challenges such as resource limitations and teacher training needs were noted, emphasizing the importance of adapting PBL to the local context. The study bridges a research gap in PBL implementation in Nepal and offers insights for integrating PBL effectively into mathematics education, paving the way for further research and improvements in pedagogical practices.